Research on Mechanical Model of Canal Lining Plates under the Effect of Frost Heaving Force - Yantao Liang; Fuping Zhang; Mingming Jing; Pengfei He (Advances in Civil Engineering)
Frost heaving damage of canal lining in cold and dry areas is one of the important causes of canal leakage. In this paper, based on the bending theory of thin plate, a mechanical model of canal lining under the action of frost heaving force is established and solved. Through parametric and engineering case analysis, the following conclusions are drawn: under the action of frost heaving force, the bending moment, shear force, and internal force of the slope plate show a nonuniform distribution, and the maximum values of bending moment Mx and normal stress σx are close to the bottom third of the slope, which is consistent with the existing research and engineering practice. Compared with the theory of beam, the results of the theory of thin plates show that the internal forces and stresses increase at the free boundary (longitudinal expansion joint). The bending moment Mxy and stress τxy are maximum at the four corners of the plate: although the numerical magnitude is lower than that of Mx, it may cause stress concentration to damage the lining plate and thus cause break. The shear force at the longitudinal expansion joint may lead to fracture of the joint material, which needs to be considered in the design process. Due to the uniform distribution of the frost heaving force on the bottom plate lining, its deflection, internal forces, and stresses also show a uniform distribution. The research results can provide scientific reference for the design and operation and maintenance of water transmission canal lining in cold areas.